Changes in the standard freezing depth of seasonally frozen ground in China over the last 50 years - Shuo Wang; Zuo-Jun Ning; You-Hua Ran; Wei Cao; Er-Xing Peng; Chen-Yang Peng; Ji-Chun Wu; Bing-Quan Wang; Yu Sheng (Arctic, Antarctic, and Alpine Research)
In recent years, under the influence of global warming, the freezing depth of seasonally frozen ground (SFG) has decreased at an accelerating rate. This has affected engineering and construction insofar as accurate determinations are needed of SFG areas and the amount of frost heaving. In this study, a method of deriving the E-factor using the improved Stefan formula was used to study changes in the standard freezing depth (SFD) of SFG in China. The method was used to reveal the trends and patterns of changes in the SFD of SFG over the past fifty years. The study relied on ERA5L and reanalysis data and empirical formulas for standard sites in China’s SFG regions. Raster data of the interdecadal SFD in SFG areas of China from 1971 to 2020 were generated to analyze changes in the SFD. Our results show that in the past fifty years, the SFD in China’s SFG areas has shown a downward trend, with the SFD changing at an average rate of −6.749 cm/10a years. The average SFD in the 1970s, 1980s, 1990s, 2000s, and 2010s was 111.31, 107.13, 95.69, 89.84, and 86.21 cm, respectively. From the overall performance of the SFD in different decadal periods, the SFD in central and northeast China changed sharply within the range of 35° N to 50° N in SFG regions. The boundary lines of low-value SFDs expanded sharply to the north as the latitude increased, and the boundary lines of high-value SFDs contracted sharply.